THE POSSIBILITY OF CORRECTION OF ENDOTHELIAL DYSFUNCTION IN PATIENTS WITH CORONARY ARTERY DISEASE AND METABOLIC SYNDROME AFTER PERCUTANEOUS CORONARY INTERVENTION FOR ACUTE CORONARY SYNDROME WITHOUT ST-SEGMENT ELEVATION - Якименко, О.О.; Холопов, Л.С.; Чумаченко, Н.В. (World of Medicine and Biology, 2015)
Objective: To investigate peculiarities of patients with coronary heart disease and metabolic syndrome (MS), underwent primary percutaneous coronary intervention (PCI) for acute coronary syndrome without ST-segment elevation (ACS nST); to increase the effectiveness of patients’ treatment by correcting of endothelial dysfunction (ED) with the additional long-term therapy by trimetazidine. Materials and Methods: 66 patients (M / F = 46 / 66) were divided into two groups by simple randomization. Group I (n = 31) received standard therapy; group II (n = 35) was additionally treated with trimetazidine 35 mg BID for 1 year. Asymmetric Dimethyl-L-Arhynyn (ADMA) and high-sensitivity C-reactive protein (hs-CRP) blood levels were investigated in all patients. Results. The period of follow-up was 11.2 ± 1.43 months. The number of patients with criteria of MS decreased to 24 (74.2 %) in group I and 27 (77.1 %) in group II. We received lower levels of low-density lipoproteins (3.96 ± 0.62, mmol / L) and very-low-density lipoproteins (0.78 ± 0.09, mmol / L) in group II compared to group I (4.29 ± 0.71, mmol / L and 0.78 ± 0.09, mmol / L, respectively), p